Molecular epidemiology and characterization of virulence genes of community-acquired and hospital-acquired methicillin-resistant staphylococcus aureus isolates in Colombia (2013)
Objective: To determine the molecular epidemiology and presence of virulence genes in communityacquired (CA) and hospital-acquired (HA) methicillin-resistant Staphylococcus aureus (MRSA) isolates and their relationship to clinical outcomes. Methods: An observational and prospective study of infections caused by MRSA was conducted between June 2006 and December 2007 across seven hospitals in three Colombian cities. MRSA isolates were analyzed for SCCmec. Also, pulsed-field gel electrophoresis and multilocus sequence typing were performed and 25 virulence genes were identified. Results: Two hundred and seventy isolates were collected from 262 adult hospital patients with MRSA infections. Overall, 68% of the isolates were classified as HA-MRSA and 32% as CA-MRSA. We identified differences in the patterns of virulence genes: 85% of HA-MRSA isolates possessed the enterotoxin gene cluster (egc), whereas 92% of CA-MRSA isolates possessed the lukF-PV/lukS-PV genes. Multivariate analysis showed an increased risk of mortality for seg (p = 0.001, odds ratio 4.73) and a protective effect for eta (p = 0.018, odds ratio 0.33). Conclusions: Our study confirms that three clones of MRSA predominantly circulate in Colombia: a Chilean clone, a pediatric clone that causes HA-MRSA infections, and a USA300-related clone (SCCmec IVc) in CA-MRSA infections, which differ in the content of clinically important virulence genes. This study confirms that PVL is not a determinant of severity or mortality in CA-MRSA infections. 2013 International Society for Infectious Diseases. Published by Elsevier Ltd. All rights reserved.